Woman with Crutch - Horace Bristol:::Creator::::::::::::
Woman with Crutch. Horace Bristol was an American Photojournalist who travelled with Steinbeck in 1938 and documented the migrant families. Bristol used the characters from Steinbeck's novel to title his photographs and Twentieth Century Fox used Bristol's photographs of real migrants to assist in the casting of The Grapes of Wrath. RESTRICTED USE